(untitled) (Jurnal Teknologi (Sciences & Engineering), 2018)
The failures of the flexible pavements are not only caused by harsh climatic conditions prevailing in most of the tropical countries but also due to increase in traffic. The ethylene vinyl acetate (EVA) modification of the bitumen can strengthen the properties of binders and also improve the quality of bitumen used for pavements construction. This paper reports the changes in physical and rheological properties of unaged 80-100 grade bitumen modified with different percentages of EVA and compared with the properties of PG 76 binder. The penetration, softening point and viscosity properties were studied. The rheological properties were measured using dynamic shear rheometer and the test was performed at temperatures ranging from 46 to 76 â°C at intervals of 6 â°C. It was noted that, after modification, the properties of binders had improved. The results show that 5% EVA content by weight in modified binder is adequate in terms of physical and rheological properties studied. In addition, the properties of 5% EVA modified 80-100 grade bitumen are similar to PG 76 binder.